2016
DOI: 10.3762/bjnano.7.104
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and simulation-based investigation of He, Ne and Ar irradiation of polymers for ion microscopy

Abstract: SummarySecondary ion mass spectrometry (SIMS) on the helium ion microscope (HIM) promises higher lateral resolution than on classical SIMS instruments. However, full advantage of this new technique can only be obtained when the interaction of He+ or Ne+ primary ions with the sample is fully controlled. In this work we investigate how He+ and Ne+ bombardment influences roughness formation and preferential sputtering for polymer samples and how they compare to Ar+ primary ions used in classical SIMS by combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 67 publications
0
17
0
Order By: Relevance
“…The amount of W is above 20% in the top half of the deposit, close to the surface, but decreases to below 10% in the bottom half of the deposit, near the substrate. In order to understand this behavior, simulations on 30 kV Ga + irradiation at a normal incidence of a 30 nm thick W(CO) 6 film on a silicon substrate have been performed using the SDTRIMSP code [56], which is based on TRIM [57,58] but allows for dynamics simulations, modelling ion-beam processes as a function of fluence while taking diffusion processes into account [59,60]. For the simulations in this work, the KrC potential has been used for interatomic interactions, the Oen-Robinson model for electronic stopping, and the Gauss-Mehler method with 16 pivots for integration.…”
Section: W-c Deposits Grown By Cryo-fibidmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of W is above 20% in the top half of the deposit, close to the surface, but decreases to below 10% in the bottom half of the deposit, near the substrate. In order to understand this behavior, simulations on 30 kV Ga + irradiation at a normal incidence of a 30 nm thick W(CO) 6 film on a silicon substrate have been performed using the SDTRIMSP code [56], which is based on TRIM [57,58] but allows for dynamics simulations, modelling ion-beam processes as a function of fluence while taking diffusion processes into account [59,60]. For the simulations in this work, the KrC potential has been used for interatomic interactions, the Oen-Robinson model for electronic stopping, and the Gauss-Mehler method with 16 pivots for integration.…”
Section: W-c Deposits Grown By Cryo-fibidmentioning
confidence: 99%
“…However, this process could be relevant for the diffusion of carbon and oxygen atoms under Ga irradiation in Cryo-FIBID, meaning that the surface concentrations of oxygen and carbon in the simulations might be overestimated and that of tungsten underestimated. In a previous study on the rare gas ion irradiation of polymer samples, including diffusion processes was essential for a correct modelling of the processes under ion irradiation [60,61].…”
Section: W-c Deposits Grown By Cryo-fibidmentioning
confidence: 99%
“…In the PTFE layers, fluorine and carbon have a similar mass, leading to the atomic mixing of both species. Accumulation of helium inside the sample is avoided by the relatively high diffusion coefficients of helium in polymers [30]. The important atomic mixing combined with the low sputtering yields makes 1 keV He + bombardment unsuited for the depth profiling of 10 nm polymer films.…”
Section: Resultsmentioning
confidence: 99%
“…This is required for the simulation of helium, neon and argon ion bombardment of polymer samples. The diffusion coefficients for the different rare gas species have been taken from a previous work [30]. The irradiation was simulated for 1 keV and 20 keV ion impacts at normal incidence which corresponds to experimental conditions for depth profiling and imaging in SIMS.…”
Section: Resultsmentioning
confidence: 99%
“…All atoms in the lipid matrix of the stratum corneum are heavier than helium, so atoms are sputtered mostly by the first mechanism described in Section 4.1.1. Investigation of sputtering of polymers by high energy (1 keV) He and Ar ions demonstrated that light atoms such as hydrogen are sputtered at first, followed by heavier carbon and oxygen [50]. On the other hand, the penetration depth increases with decreasing atomic mass, which means that an atomic mass of helium allows penetration deeper inside the surface than argon [51].…”
Section: Helium Bombardment/helium Plasmamentioning
confidence: 99%